(untitled) (Fiep Bulletin - online, 2016)
The objective of the following study is to identify if the public recreational spaces in the city of Cascavel – PR offer an architectural structure that allows the access of people with physical disability (wheelchair users). The study is characterized as a field descriptive research, in which was conducted a visit with a disabled person (wheelchair user) in four public recreational spaces: The town Lake, Ciro Nardi sports complex, Tarquínio Park and the Zoo. We intend, through the research, point out the physical structures of leisure offered by these spaces; we also want to discover the main difficulties that a physically disabled person have to use these public spaces for leisure and identify how the professional of physical education can act with these people in public recreational spaces. The data was collected with a questionnaire with opened and closed questions; in addition, all the architectural structures were registered through photographical records, which were compared with those proposed by the literature that described how to adapt unfavorable environments. The results showed that all visited public spaces have a lack of adjustments in the physical structures of the bathrooms, the drinking fountains and the access ramps to the sidewalks, making the access difficult for people with physical disabilities; on this scenario, disabled people have no conditions to access properly these public spaces and practice recreational activities. The research also pointed out the lack of trained people to guide and to provide leisure activities, and insufficient efforts from the government authorities to promote actions to ensure the rights of people with disabilities to exercise their rights as citizens, and be able to properly access public spaces to do these recreational activities.